Relationship between Perceived Benefits/Barriers and Decisional Balance with Stages of Change for Physical Activity among High School Students in Bandar Abbas - Amin Ghanbarnejad; Sedigheh Sadat Tavafian; Teamur Aghamolaei (Tehran University of Medical Sciences, 2012)
Background & Aim: This study aimed to assess relationship between perceived benefits/barriers and decisional balance with stages of change for physical activity among high school students in Bandar Abbas, Iran.Methods & Materials: This cross-sectional study was conducted in high schools of Bandar Abbas, in the south of Iran. A total of 422 high school students were selected. Twenty two participants did not fill out questionnaires completely. A total of 400 questionnaires were analyzed (response rate=94.8%). The perceived benefits/ barriers to exercise and decisional balance were assessed using the Exercise Benefits/Barriers Scale; and stages of change were assessed using the Physical Activity staging. Data were analyzed in the SPSS v.16.Results: The mean age of the participants was 15.9 (SD=1.1) ranging from 14 to 18 years. More than half of the participants (51.8%) were male and 48.2% were female. About half of the participants (49.2%) were engaged in regular physical activities. Fifteen per cent of the participants in the precontemplation stage, 15.8% in the contemplation stage, 20% in preparation stage, 15.8% in action stage, and 33.4% in maintenance stage for physical activity. From precontemplation stage to maintenance stage, the perceived benefits and decisional balance were increased and the perceived barriers was decreased.Conclusion: The results of this study are in line with the Transtheoretical model. This model can be used as a framework to design interventions for improving physical activity in population.